Performance Analyse of Air Mixed and Displacement Ventilatilation System in Office Room Base on Computational Fluid Dynamic - Bambang Iskandariawan; Paulus Indiyono; Herman Sasongko; Prabowoa Prabowo (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2009)
Air ventilation system is required for improvement as well as maintenance room air circumstance which is always clean in the whole day. Effective ventilation will enhance thermal comfort and indoor air quality therefore the productivity of occupant is expected also becomes mo-re intense. This research deals with the influence of supply air diffuser position concerning to thermal comfort and in-door air quality viewpoints. It is inspected four categories of air ventilation system: mixed and displacement ventila-tion used for air supply diffuser position in the centre and at the side of the room. Thermal comfort aspect is demons-trated through velocity and temperature of the room air without considering the value of relative humidity and room surface temperature average). On the other side the indoor air quality is focused on the intensity of the CO2 gas concentration which is appear inside the room gas. It applies Fluent 6.2 as computational fluid dynamics (CFD) simulation, some research variables are exploited. Office room model is generated in GAMBIT software create par-ticular office room design. Analyse result prove that the displacement centre ventilation system has more capability in the handling of room heat in addition to contaminant gas compare to the others.